The construction of a royal and dinastic tradition for the Yaro in Guaman Pomas’s chronicle - Arana Bustamante, Luis Manuel (2015)
I study here some selected passages of Nueva Corónica y Buen Gobierno for an analysis of the construction of a pseudohistorical tradition for his descendance line. Abounding in details about the supposed Yaro reign of his grandfather, the Andean chronicler reproduces a relation of kings of this kingdom or empire, situated in Huánuco region, an affirmation interpreted too literally in another occasions. I examine here this historiographic construction from his principles of time computation and historicity in Andean civilization and in this chronicler in particular.